EFEKTIVITAS SISTEM PELEPASAN INFORMASI MEDIS PENGGUNA ASURANSI SWASTA DENGAN TAMPILAN MOBILE PADA RUMAH SAKIT DAERAH MANGUSADA KABUPATEN BADUNG - Ayu Putu Sriantary (Health Care Media, 2022)
The Mangusada Regional Hospital (RSD) provides medical information release services for private insurance purposes. The retrieval and recording of the medical information release reports are still carried out manually, the applicant comes directly to the hospital. The time for taking the release of medical information in accordance with standard operating procedures (SOPs) is 2 to 7 days. The purpose of this study was to determine the effectiveness of the medical information release system for private insurance users with a mobile display at the time of retrieval of medical information for insurance purposes. This research is quantitative research using a pre-experimental design with the type of one-group pretest-posttest design. The system development stage analysis method uses the system development life cycle (SDLC). The results of the study using the usability test obtained a percentage value of 79.58% which can be categorized as "Good". The results of the hypothesis research using the Wilcoxon signed rank test got a significant value of 0.013 so 0.013 <0.050. Based on the conclusion of this study, the use of medical information release system with a mobile display of private insurance users is successful in retrieving medical information release requests for medical discharge applications, and patient information in the medical discharge application process, and simplifies monthly reporting.